(untitled) (One Health & Risk Management, 2021)
Introduction. The outbreaks of Coronavirus Disease, popularly known as COVID-19 in November 2019 created new dimension in the way people live, relate and interact across the world. Despite the fact that this disease caused a lot of deaths and illnesses in many countries, many people still doubt its existence. Public health experts have explained that the infectious disease transmitted between animals and humans, and is caused by new form of coronavirus (SARS-CoV-2) which had been previously identified in human beings and first reported by World Health Organisations (WHO) in Wuhan, China on 31st December, 2019. Since then, the virus continues to spread across the world with reported cases in almost all countries that carry out some tests for their citizens. Many of these cases of transmissions have been reported in indoor locations such as restaurants, places of worship, schools, hotels, nightclubs, airports, game centres, parks and markets. Material and methods. This study looks at the myths and realities of the virus’ existence through a perception study in selected countries of West Africa. The study was qualitatively induced with data generated from interviews with respondents in Nigeria, Cameroon and Niger. Results. The study revealed that despite the scientifically proven evidence on the existence of COVID-19, large percentages of people do not agree with the existence of the virus in all the selected countries. Culture played huge role in this perception, as the study revealed that COVID-19 is still a myth in West Africa with citizens either disbelieving in it entirely, considered it a European based disease or less deadly compared to the existing problems in the continent. The high level of corruption driven by bad governance has made citizens lose trust in what government advocates for, or laws it introduces in relation to those things. The high level of poverty and illiteracy make people think about entirely different problems other than COVID-19. Many do not consider as a killer disease due to hunger and poor state of living. There is further a misperception in some communities of the selected countries that the virus does not catch youths and teenagers, but old people only. Some citizens also believe that the hot sun in some parts of the countries will not allow the virus to survive, or infect anyone as the sunlight is a natural cure for such viruses. Nevertheless, there has been high level of awareness on social media, radio stations and television stations, as well as the use of posters, bill boards and physical community engagements organised by civil society groups, development organisations and government agencies. Many sets of meetings have also been organised between and among actors and stakeholders in development space in an effort to avert the spread of the virus. Conclusions. The study concluded therefore that COVID-19 remains a myth in West Africa till date, and requires huge effort to overcome this. Changing this narrative will require addressing the root challenges which includes investing hugely in human capital development.